2019
DOI: 10.1016/j.fsi.2019.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Survival and immune response of white shrimp Litopenaeus vannamei following single and concurrent infections with WSSV and Vibrio parahaemolyticus

Abstract: The survival and immune responses of Litopenaeus vannamei were evaluated during white spot syndrome virus (WSSV) or Vibrio parahaemolyticus single and concurrent infections. The mortality, WSSV load, activities of 4 immune enzymes: acid phosphatase (ACP), alkaline phosphatase (AKP), peroxidase (POD) and superoxide dismutase (SOD), and the transcription of Evolutionarily Conserved Signaling Intermediate in Toll pathways of L.vannamei (LvECSIT) were quantified at 0, 3, 6, 12, 24, 48, 72 and 96 h post-infection (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The activities of SOD and CAT, and the MDA levels of Clarias gariepinus in clean region from Orontes river were higher than those in the polluted regions (Turan et al, 2020). The SOD activity of L. vannamei injected Vibro parahaemolyticus at 3h, 6h and 12h were higher than that in the control group (Pang et al, 2019). These results indicated that organism with lower oxidative stress had a reduced need for endogenous antioxidant enzymes.…”
Section: Effects Of Dietary Resveratrol Supplementation On Antioxidant Capacitymentioning
confidence: 71%
“…The activities of SOD and CAT, and the MDA levels of Clarias gariepinus in clean region from Orontes river were higher than those in the polluted regions (Turan et al, 2020). The SOD activity of L. vannamei injected Vibro parahaemolyticus at 3h, 6h and 12h were higher than that in the control group (Pang et al, 2019). These results indicated that organism with lower oxidative stress had a reduced need for endogenous antioxidant enzymes.…”
Section: Effects Of Dietary Resveratrol Supplementation On Antioxidant Capacitymentioning
confidence: 71%
“…Dietary yeasty Ast significantly increased resistance to V. parahaemolyticus according to the LT 50 results in the current study, which may be contributing to the anti-bacterial effects, which indicated that dietary Ast could suppress V. parahaemolyticus infection. However, V. parahaemolyticus is a conditional pathogen: the pathogenicity is triggered by physical stressors that disrupt the delicate balance between aquatic animals and surrounding environments ( Pang et al, 2019 ). Thus, improved immune status by inducing AST, ALT, AKP, and SOD in the shrimp by dietary Ast is also one of the primary reasons to defend against pathogenic infections in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Contents of TP, ACP, AKP and LZM in haemolymph are often regarded as the relevant indicators to evaluate immune regulation of crustaceans (F. Liu, Qu, et al, 2020; Ray et al, 2020). And the decrease in these parameters implies a depressed immune modulation and disease resistance (F. Liu, Qu, et al, 2020; Pang et al, 2019; Qin et al, 2012; Yuan et al, 2019). However, partial replacement of FO with BT could reverse the declining effect of TP, ACP and LZM contents, which can be explained that FB diet still had enough essential fatty acids to improve immune function (Emery et al, 2014).…”
Section: Discussionmentioning
confidence: 99%